2021
DOI: 10.1177/11206721211064015
|View full text |Cite
|
Sign up to set email alerts
|

Functional metagenomic profile of the lacrimal sac microbial communities in primary acquired nasolacrimal duct obstruction: The Lacriome paper 2

Abstract: Purpose To study the functional metagenomic profile of the microbes isolated from the lacrimal sac of patients with primary acquired nasolacrimal duct obstruction. Methods A prospective study was performed on 10 consecutive lacrimal sac samples obtained for the metagenomic analysis from patients with primary acquired nasolacrimal duct obstruction ( who underwent endoscopic dacryocystorhinostomy at a tertiary care Dacryology service. The samples were collected intraoperatively soon after a full-length lacrimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…15 The functional profiling of microbial communities in PANDO has demonstrated their involvement in a wide range of metabolic processes, environmental information processes, genetic information processes, cell cycle regulation, dormancy, and sporulation. 16 In comparison, the metagenomic profile of infectious canaliculitis is quite distinct from that of PANDO, as demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…15 The functional profiling of microbial communities in PANDO has demonstrated their involvement in a wide range of metabolic processes, environmental information processes, genetic information processes, cell cycle regulation, dormancy, and sporulation. 16 In comparison, the metagenomic profile of infectious canaliculitis is quite distinct from that of PANDO, as demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…To comprehend the fundamental etiopathogenesis of PANDO, the concept of the ‘lacriome’ was recently introduced, defining it as the collective microenvironments of the lacrimal drainage system. 18 21 Metagenomic profiling of organisms isolated from PANDO patients commonly reveals the presence of bacteria, followed by viruses and archaea. 22 In this study, we observed bacterial colonies in 22.6% of mucinous obstruction cases, but none in membranous obstruction, with a significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Functional metagenomics of the microbial isolates from lacrimal stents was mostly similar to those isolated from the lacrimal sac in patients with primary acquired nasolacrimal duct obstruction. 21 The stent microbial communities were involved in several metabolic, environmental, and genetic information processes. The Kyoto Encyclopedia of Genes and Genomes and Cluster of Orthologous Genes annotation profiles showed high expression of exodeoxyribonuclease, iron complex transport system permease, methyl-accepting chemotaxis proteins, valine-glycine repeat G proteins, 3-oxacyl reductase fabG protein, and regulatory subunits of transposase, bacterial NADPH-aldehyde dehydrogenase, and multidrug efflux pumps (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The whole shotgun metagenome sequencing technique was similar to the one published earlier. 20,21 In brief, following the DNA extraction and quality assessment, the Qubit 4.0 fluorometer and DNA HS assay kit (Thermo Fischer Scientific, MA, U.S.A.) were used to quantify the final libraries. Insert size of the library was identified using the highly sensitive D1000 screentapes on Tapestation 4150 (Agilent, CA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%